Political Equality in the American States: What We Know and What We Still Need to Learn. (March 2017) - Flavin, Patrick
This review essay illustrates the importance and utility of studying political equality among rich and poor citizens at the state level, reviews what is known in three key areas of political equality research in the states (unequal rates of political participation, unequal government responsiveness to citizens' political opinions, and public policy and inequality), and suggests possible future avenues of inquiry. The ultimate aim is to organize and integrate existing knowledge about political equality in the American states and spur future investigations that will further extend understanding among researchers and practitioners of state politics.